Effect of Yersinia pestis on the Soil Nematodes Panagrolaimus sp. from the Gorno-Altai High-Mountain Focus of Plague - M. A. Makashova; E. G. Oglodin; N. A. Sharapova; A. E. Samoilov; G. A. Eroshenko; V. V. Kutyrev (Проблемы особо опасных инфекций, 2023)
The aim of the work was to study interaction of Yersinia pestis with soil nematodes isolated on the territory of the Gorno-Altai high-mountain plague focus. Materials and methods. We used the fluorescent Y. pestis strain KM2083, a derivative of the natural strain of the 4.ANT phylogenetic line, the antique biovar of the main subspecies, and a nematode culture isolated in the same area of the Gorno-Altai plague focus. The taxonomy of nematodes was determined by the region of the 18S rRNA gene; phylogenetic analysis was performed using the Maximum Likelihood method based on the Tamura-Nei model in the Mega 7.0 software. The interaction of the Y. pestis KM2083 strain and the nematodes was studied during cultivation on a solid NGM agar medium. Nematodes were observed using microscopes Stemi-2000C (Carl Zeiss, Germany) and Axio Imager Z2 (Carl Zeiss, Germany). Results and discussion. It has been established that the nematodes from the Gorno-Altai high-mountain plague focus used in the work belong to the genus Panagrolaimus. Cultivation of nematodes on the lawn of the Y. pestis strain of the main subspecies of antique biovar, the 4.ANT phylogenetic line for 24 hours did not lead to a reduction in the lifespan of nematodes compared to the control sample, which indicates the absence of toxicity of the used strain towards Panagrolaimus nematodes. On the cuticle of nematodes, the formation of a biofilm in the genital area and tail has been noted, and accumulations of fluorescent cells of the plague pathogen observed in the digestive tract. The data obtained can indicate the ability of nematodes to carry the plague pathogen in the soil biocoenosis.